To Study Consumer ‘S Perceptions About EASE of Use of Online Banking in Ahmedabad - Mehta, Dhyey; Chauhan, Diya; Vidani, Jignesh (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This paper gives an insight on how the residents of Ahmedabad prefer digital banking and what relationship is there between customer use level of usage for a particular activity (Use practice) on which consumer behaviour model being influential, distinctive or remain constrain. 8) To this extent, the research seeks to understand how digital banking services have an impact on satisfaction levels and different insights related to it such as convenience, security and quality of service. An observational study using a mixed-methods approach was conducted, by means of an interviewer-administered questionnaire among 101 patients. Fund transfer and payments are found to be the top driver in usage of digital banking services, as per the analysis done. Spoon-feeding the details for those who are interested: Interesting associations between some demographic variables and banking activities were identified using statistical tools (Chi-Square/Correlation tests). Results show a strong relationship between user satisfaction and digital banking services, even though the strength of that correlation was quite low. Also, analysis on the perceptions of digital financial services among university students in Mexico reveals considerable satisfaction with debit card and mobile banking service. The study had also tracked general patterns in digital banking and recorded a spike in online transactions fuelled by technology upgrades as well government-sponsored policies such as ‘Digital India.’ But at the same time, worries of regarding security and internet reliance remain on everybody's mind too. The findings highlight the issues that banks have to tackle and improve upon.